The Effect of Individual and Leadership Characteristics Toward Research Productivity with Institutional Characteristics as a Mediator Variable: Analysis Toward Academic Lecturers in the Faculty of Economics and Faculty of Linguistic and Arts at University - Lase, Evi Permata Sari; Hartijasti, Yanki (UI Scholars Hub, 2018)
This research analyses the influence of both individual and leadership characteristics on research productivity. mediated by institutional characteristics. of the lecturers in the Faculty of Economics and the Faculty of Languages and Arts at the University of X in Jakarta. We distributed a questionnaire with closed questions to 100 lecturers who are not department heads and hold master’s degrees or higher. We then performed a quantitative analysis of mediation using SPSS software. The results indicate that the effect of individual characteristics on research productivity is partially mediated by institutional characteristics. and that the effect of leadership characteristics on research productivity is fully mediated by institutional characteristics.